Penerapan Nilai-Nilai Serviam di Sekolah Ursulin Jenjang SMP: Penerapan Nilai-Nilai Serviam di Sekolah Ursulin Jenjang SMP - Tuba, Elisabeth; Mohammad Ali (Jurnal Pendidikan dan Kebudayaan Missio, 2023)
Integrative education which is not only oriented towards educating the nation's children intellectually, but also spiritually, socially-emotionally and kinesthetically, must be the concern of all education stakeholders. This is also a concern of educational stakeholders in Ursuline schools. Ursuline schools have main values or core values, namely Serviam which means "I Serve". Serviam's values include love and compassion, integrity, courage and sincerity, unity, totality and service. These values are sourced from holy books, Church teachings and the spirituality of Santa Angela. How is the application of these values in Ursuline education? So far, there has been no research on this. This research was conducted to fill this gap with the aim of exploring and describing a model for implementing Serviam's values in education in Ursuline schools. The method used is a qualitative method. Data obtained by interview technique, observation and documentation study. Data validation was carried out by means of technique and source triangulation. Furthermore, the data were analyzed with the stages of data reduction, data presentation, and drawing conclusions. The results showed that the application of Serviam's values was carried out through (1) learning activities in all subjects both in planning (96.3% of teachers prepared lesson plans with Serviam's character), implementation (88.9% of teachers implemented lesson plans with Serviam's character in learning) and assessment (100% of teachers filled out an attitude assessment journal containing Serviam's character values); (2) developing school culture through routine activities, spontaneous activities, exemplary and conditioning; (3) extracurricular activities and (4) daily activities at home and in the community. This research contributes to enriching the literature on character education and provides important input for stakeholders regarding the development of character education that is integrative and systematic so that it can be input in conducting prove and improve curriculum construction at the document level and practice in the field so that students have a calling in life. and ready to serve in his life.